IMPLEMENTATION OF CAREER GUIDANCE FOR STUDENTS IN LATVIAN GENERAL SECONDARY EDUCATION INSTITUTIONS - Korna-Opincāne, Evita; Katane, Irēna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Changes shaping the labour market in the 21st century mark new guidelines for general education schools. Transformation of the education system of the state is defined by variable social and economic conditions in Latvia, Europe and the world. In that context, it is important to ensure the implementation of career guidance in schools. In various general education schools of Latvia, the implementation of career guidance is distinctly different. The availability of career guidance for students is insufficient, the guidance is not rendered systematically and purposefully, there are differences among city schools and village schools and it is also affected by the number of students in educational institutions and by the availability of various career specialists. The aim of the research is to examine the diversity of career guidance in various general secondary education institutions. The research explores, analyses and evaluates the data acquired from general secondary education schools of Latvia. The results of the research will provide the basis for elaboration of career guidance models, their experimental approbation and implementation in various Latvian schools. Research took place in the framework of European Social Fund 2014-2020 Operational Programme “Growth and Employment”.